2019
DOI: 10.1093/mnras/stz2934
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning predictions of galaxy merger stage and the importance of observational realism

Abstract: Machine learning is becoming a popular tool to quantify galaxy morphologies and identify mergers. However, this technique relies on using an appropriate set of training data to be successful. By combining hydrodynamical simulations, synthetic observations and convolutional neural networks (CNNs), we quantitatively assess how realistic simulated galaxy images must be in order to reliably classify mergers. Specifically, we compare the performance of CNNs trained with two types of galaxy images, stellar maps and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 148 publications
(204 reference statements)
2
92
1
Order By: Relevance
“…Although there is no mathematical reason that such indicators could not be applied to any 2-dimensional distribution, the limitations of realistic data may impose practical impediments. For this reason, it has become a common approach to add observational realism to simulated data, in order to fairly compare derived properties (Bottrell et al 2017a,b;Huertas-Company et al 2019;Bottrell et al 2019b;Zanisi et al 2020;Ferreira et al 2020). Our approach is therefore to use simulations of galaxies, for which we can measure 'true' values of a given morphology metric, before adding noise (e.g.…”
Section: Simulated Galaxy Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no mathematical reason that such indicators could not be applied to any 2-dimensional distribution, the limitations of realistic data may impose practical impediments. For this reason, it has become a common approach to add observational realism to simulated data, in order to fairly compare derived properties (Bottrell et al 2017a,b;Huertas-Company et al 2019;Bottrell et al 2019b;Zanisi et al 2020;Ferreira et al 2020). Our approach is therefore to use simulations of galaxies, for which we can measure 'true' values of a given morphology metric, before adding noise (e.g.…”
Section: Simulated Galaxy Imagesmentioning
confidence: 99%
“…The first is through crowd-sourcing, whereby the power of the human brain continues to be tapped, through the contributions of citizen scientists (Darg et al 2010;Lintott et al 2011;Casteels et al 2014;Simmons et al 2017;Willett et al 2017). Recently, artificial intelligence is replacing humans and machine learning algorithms are increasingly being applied to the challenge of large imaging datasets, either for general morphological classification (Huertas-Company et al 2015;Domínguez Sánchez et al 2019;Cheng et al 2020;Walmsley et al 2021) or the identification of particular galaxy types/features (Bottrell et al 2019b;Pearson et al 2019;Ferreira et al 2020;Bickley et al 2021). An alternative automated approach, which has been in use for several decades, is to compute some metric of the galaxy's light distribution, a technique which is readily applicable to large datasets.…”
Section: Introductionmentioning
confidence: 99%
“…However observational works must ascertain the merging state of a galaxy from only an instantaneous (often pre-coalescence) snapshot. Thus a truly fair comparison would require us to apply observational techniques to synthetic images to estimate a galaxy's current merging state (similar to Lahén et al 2018;Bottrell et al 2019;Snyder et al 2019, for example), but this is beyond the scope of this study. We can, however, qualitatively compare our results to the observational studies.…”
Section: Comparing To Observationsmentioning
confidence: 99%
“…For more details about RealSim, we refer the reader to the original papers. Bottrell et al (2019) have shown that the including the correct level of realism in mock observations is crucial when using neural networks for classification tasks.…”
Section: Observational Realismmentioning
confidence: 99%